PENGEMBANGAN BUKU AJAR METODE NUMERIK BERBASIS KONSTRUKTIVISME DI IAIN BATUSANGKAR - Christina Khaidir (Ta'dib, 2016)
AbstractThe purpose of this research is to develop textbook materials on constructivism-based numeric method.  This idea is based on the reality found the field that some textbook materials on that issue are not relevant anymore. This research used research and development using Plom model. The stages consist of front-end-analysis, prototype, and assessment. Data were validated using experts’ and practical validation. The textbook was validated by experts who were competence in their academic field. Based on the experts’ validation result, the textbook was deemed valid. In terms of practicality, the textbook was also considered practical.Kata Kunci: Buku Ajar Metode Numerik, Pendekatan Konstruktivisme